2022
DOI: 10.1101/2022.12.01.22282769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel decision-making tool for first-line treatment selection in metastatic non-small cell lung cancer based on plasma proteome profiling

Abstract: Importance: Advanced stage non-small cell lung cancer (NSCLC) patients with no driver mutations are typically treated with immune checkpoint inhibitor (ICI)-based therapy, either in the form of monotherapy or concurrently with chemotherapy, while treatment modality selection is based mainly on programmed death ligand 1 (PD-L1) expression levels in the tumor. However, PD-L1 assays are only moderately predictive of therapeutic benefit. Objective: To develop a novel decision-making tool for physicians treating NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There are more sophisticated (and more costly) blood-based proteomic assays to assess the host. VeriStrat ® and PROphet ® are commercial proprietary blood-based proteomic assays that reflect host inflammatory proteins ( 12 , 13 ). They have both been evaluated as predictive host immune biomarkers in first-line IO treatment in metastatic NSCLC patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are more sophisticated (and more costly) blood-based proteomic assays to assess the host. VeriStrat ® and PROphet ® are commercial proprietary blood-based proteomic assays that reflect host inflammatory proteins ( 12 , 13 ). They have both been evaluated as predictive host immune biomarkers in first-line IO treatment in metastatic NSCLC patients.…”
mentioning
confidence: 99%
“…In the multi-institutional INSIGHT registry study, patients with tissue PD-L1 ≥50% and VeriStrat ® poor/HIC-C significantly benefited from chemoIO compared to monoIO, whereas patients VeriStrat ® good/HIC-H had a similar benefit whether chemoIO or monoIO ( 12 ). In the international multi-institutional PROPHETIC study, PROphet ® negative patients with tissue PD-L1 ≥50% demonstrated a significantly better overall survival with chemoIO compared to monoIO ( 13 ). However, there was no difference between chemoIO and monoIO outcomes in PROphet ® positive patients.…”
mentioning
confidence: 99%